Measuring Children's Ethnic Prejudice - Sugoto, Srisiuni; Sutjipto, Sari Dewi; Yudiarso, Ananta; Yusof, Aminuddin Mohd. (ANIMA Indonesian Psychological Journal, 2010)
The validity of Doyle and Aboud ‘s Multi-Response Racial Attitude (MRA) test was examined using Surabaya’s Javanese (SJ) and Chinese (SC) children’s pictures projected in multimedia, including the development of racial prejudice among the participants. MRA (Kline, 2005) uses six children pictures from three different ethnic groups. To encourage children’s responses, their attitude was measured through a computer program. Children from 5-6 years (N = 82) and from 9-11 years (N = 86) from Muslim, Christian, public and private schools were participating in this study. A criterion-related validity was tested by correlating the new MRA test and the Ethnocentrism Scale (E-scale) test of prejudicial attitude. Only the third set of MRA’s test is correlated significantly with E-scale (r = .469, p< .05). Older SJ children seems to develop prejudice more than the younger ones, on the other hand the SC children have much less prejudice towards SJ children. Validitas tes Multi-Response Racial Attitude (MRA) dari Doyle and Aboud diteliti dengan memakai gambar anak Jawa (AJ) dan anak Cina (AC) yang diproyeksikan di multimedia, termasuk perkembangan prasangka rasial di antara para partisipan. MRA (Kline, 2005) memakai enam gambar anak dari tiga kelompok etnis berbeda. Untuk menyemangati anak-anak merespons, sikapnya diukur melalui program komputer. Anak-anak berusia antara 5 hingga 6 tahun (N = 82) dan antara 9 hingga 11 tahun (N = 86) berasal dari sekolah Muslim, Kristen, dan swasta berpartisipasi dalam kajian ini. Validitas terkait-kriteria diuji dengan mengorelasikan tes MRA yang baru dengan tes Ethnocentrism Scale (E-scale) sikap berprasangka. Hanya perangkat ketiga dari tes MRA berkorelasi secara bermakna dengan E-scale (r = .469, p< .05). Anak AJ dari kelompok yang lebih tua tampaknya mengembangkan prasangka lebih dari anak dari kelompok yang muda, sebaliknya AC jauh lebih sedikit prasangkanya terhadap AJ.